Pour une approche philosophique globale des inégalités - Alain Renaut; Jean-Cassien Billier (Socio, 2015)
Today three transformations characterise a philosophical approach to injustice which, while continuing to be prescriptive, is moving away from the “Kantian” versions dominant since the 1970s. This new approach, re-articulated with the social sciences, is global rather than social, non-ideal rather than ideal, and there is a greater insistence on starting with data, rather than with principles. Consequently, while redefining the status and function of principles in political philosophy, this study intends to consider the conditions and the scope of an approach based on situations of extreme inequality, under the headings of poverty, violence and risk.